Fraud threats: How organization improves the anti-fraud team quality? - Fajri, Kharisma Fatmalina; Hendi Yogi Prabowo (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This study aims to discover how the Indonesian Local Government Rural Bank improves the quality of the anti-fraud team to prevent and detect fraud based on a mechanism of the anti-fraud strategy issued by Bank Indonesia. A qualitative analysis approach was applied 12 semi-structured interviews with the anti-fraud team and related officers. The content analysis approach supported by NVivo software and has discovered several required competencies and competencies already developed by the organization’s anti-fraud team for fraud prevention and detection. This study provides a detailed discussion of how these competencies are used in the anti-fraud mechanism by identifying the gaps between the required competencies and developed competencies to give recommendations for the organization to enhance the quality of the anti-fraud team in conducting fraud prevention and detection.